Adult development and aging - Perlmutter, Marion; Hall, Elizabeth (New York : John Wiley, 1992)
Social Science
2000-07-19
Keywords: Adulthood; Aging; Human life cycle; Developmental psychology; Biological changes; Physical health; Mental health; Sensation; Intelligence; Personality; Motivation; Community involvement; Social issues; Cross culture